The morphology, inflorescence yield, and secondary metabolite accumulation in hemp type Cannabis sativa can be influenced by the R:FR ratio or the amount of short wavelength radiation in a spectrum - Kotiranta, Stiina; Pihlava, Juha-Matti; Kotilainen, Titta; Palonen, Pauliina (Elsevier BV, 2024)
The effect of light spectra on the quality of multiple crops has been established, however, the scientific evidence related to light quality, cannabis (Cannabis sativa) morphology, and the secondary metabolite accumulation in the female inflorescences is still sparse. C. sativa inflorescences harvested for pharmaceutical purposes are primarily cultivated in controlled environments for their secondary metabolite compounds, such as cannabinoids, terpenes, and flavonoids. Indoor cultivation allows precise control over the environmental parameters, including light, which impact the inflorescence yield and quality. The effect of long (far-red) and short wavelength (blue, UV-A, UV-B) radiation on the morphology, inflorescence yield, and floral cannabinoid and terpene concentrations in a cannabidiol (CBD) dominant hemp type C. sativa genotype, FINOLA, was studied in two experiments. In the first experiment, two treatments, LOW R:FR (R:FR ratio of 1) and HIGH R:FR (R:FR ratio of 11), were compared. The second experiment included four treatments with varying blue, UV-A, and UV-B radiation content (CONTROL, BLUE, UVA, and UVB). LOW R:FR ratio treatment increased plant height and decreased inflorescence yield. HIGH R:FR ratio treatment increased CBD, tetrahydrocannabivarin acid (THCVA), and cannabigerolic acid (CBGA), and the sum of measured terpene concentrations compared with the LOW R:FR ratio treatment. Short wavelength radiation treatments did not impact inflorescence yield or plant morphology. BLUE and UVB treatments increased the cannabinoid, THCVA, concentration, but no difference in the sum of measured cannabinoid concentrations was observed between the treatments. UVB treatment increased the monoterpene, myrcene, concentration, but had no impact on the sum of measured terpenes concentration. In conclusion, the morphology, yield, and secondary metabolite accumulation in C. sativa can be influenced by altering the R:FR ratio or the amount of short wavelength radiation in a spectrum.
Keywords: photobiology; controlled environment agriculture; Cannabis sativa; UVB; Far-red; CBD; Cannabinoid; Terpene